An immersive flipped classroom for learning Mandarin Chinese: design, implementation, and outcomes. Issue 7 (3rd September 2018) - Tseng, Miao-fen; Lin, Chin-Hsi; Chen, Henny
ABSTRACT: Online kindergarten to twelfth grade (K-12) language learners have usually been found to hold more negative perceptions of their courses and to perform less well academically than their face-to-face counterparts, despite the well-attested benefits of computer-mediated communication in language learning. In an attempt to improve upon such outcomes, this study designed, implemented, and evaluated a 12-day immersive online high-school Chinese-language course that included daily synchronous sessions and interactive technology-enhanced tasks, with a special emphasis on engaging the students in meaningful social interactions. Based on the analysis of the 35 participants' survey responses and their language performance, they had a very positive experience of the course, felt satisfied by it, and showed statistically significant improvement in their language skills. These findings are discussed in relation to prior studies' findings and current online-education policies and practices.